Platelets as Central Actors in Thrombosis—Reprising an Old Role and Defining a New Character - Stevens, Hannah; McFadyen, James D. (Seminars in Thrombosis and Hemostasis, 2019)
Platelets have long been considered simple anucleate cells that rapidly adhere and aggregate at sites of vascular injury. However, recent in vivo experimental data have shed new light on the platelet response to vascular injury. These data have unexpectedly revealed that platelet thrombus formation is a highly dynamic process and yields a platelet thrombus with a distinct hierarchical structure composed of a “core” of highly activated platelets and a “shell” of platelets in a low activation state. This has given rise to the concept that therapeutic targeting of the propagating thrombus shell may hold promise as a means to target thrombosis while sparing hemostasis. While platelets have been historically considered central to arterial thrombosis, they have been traditionally viewed as minor contributors to the formation of venous thrombosis. However, this concept has recently been challenged with the emergence of a large body of evidence highlighting the important proinflammatory function of platelets. The proinflammatory function of platelets is afforded by their ability to induce neutrophil extracellular trap formation, enhance leucocyte recruitment, and secrete granular contents such as high mobility group protein B1 and polyphosphate. These proinflammatory processes trigger coagulation, via the intrinsic pathway, and are central to the formation of venous thrombosis, a condition now appreciated to be a form of sterile inflammation. These data now place platelets at the center stage in orchestrating the thromboinflammatory response underpinning venous thrombosis and have provided new hope that novel platelet-targeted therapeutics may represent a safe and effective approach to prevent venous thrombosis.
Keywords: arterial thrombosis; venous thrombosis; platelets; antithrombotic; bleeding